Affects, actions and passions in Spinoza : the unity of body and mind - Jaquet, Chantal (Spinoza studies., 2018)
It is widely recognised that Spinoza ended the Cartesian dualism of body and mind by thinking through the possibility of their unity. Revisiting this generally accepted notion of psycho-physical parallelism in Spinoza, Chantal Jaquet offers a new analysis of the relation between body and mind. Looking at a range of Spinoza's texts, and using an original methodology, she analyses their unity in action through the affects that bring together a body's affection and the idea of this affection. Jaquet reveals that understanding affects, actions and passions provides the key to how the mind and body are the same individual expressed in two different ways. She presents the Spinozist model in all its complexity, illuminating its potentialities for contemporary debates on the nature of the mind-body problem.